Length-weight relationships for nine fish species from shallow lakes of the Pampa plain, Argentina - Gonzalez Sagrario, Maria de Los Angeles (2013)
This study presents length-weight relationships for nine neotropical fish species collected from four shallow lakes from the southeastern Pampean region, representing the first record for these species. Also, new sizes for six species are also provided.